2018
DOI: 10.1016/j.neuron.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The Meningeal Lymphatic System: A New Player in Neurophysiology

Abstract: Summary The nature of fluid dynamics within the brain parenchyma is a focus of intensive research. Of particular relevance is its participation in diseases associated with protein accumulation and aggregation in the brain, such as Alzheimer’s disease (AD). The meningeal lymphatic vessels of the central nervous system have recently been recognized as an important player in the complex circulation and exchange of soluble contents between the cerebrospinal fluid (CSF) and the interstitial fluid (ISF). In aging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
274
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(305 citation statements)
references
References 181 publications
(313 reference statements)
2
274
0
4
Order By: Relevance
“…In addition, it was previously believed that the brain and CNS lacked a functional lymphatic system that could aid in immunosurveillance and fluid drainage . However, recent work has revealed that lymphatic vessels do in fact exist in the meninges of the brain . These findings have prompted a reassessment of the role of the lymphatic vasculature in the CNS and its involvement in a variety of neuroimmunological disorders.…”
Section: Future Outlooksmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was previously believed that the brain and CNS lacked a functional lymphatic system that could aid in immunosurveillance and fluid drainage . However, recent work has revealed that lymphatic vessels do in fact exist in the meninges of the brain . These findings have prompted a reassessment of the role of the lymphatic vasculature in the CNS and its involvement in a variety of neuroimmunological disorders.…”
Section: Future Outlooksmentioning
confidence: 99%
“…165 However, recent work has revealed that lymphatic vessels do in fact exist in the meninges of the brain. [166][167][168] These findings have prompted a reassessment of the role of the lymphatic vasculature in the CNS and its involvement in a variety of neuroimmunological disorders. For instance, Kipnis and colleagues showed that meningeal lymphatic vessels play an essential role in draining amyloid-β peptides from cerebrospinal fluids and into cervical lymph node to maintain brain homeostasis.…”
Section: Future Outlook Smentioning
confidence: 99%
“…Trafficking of immune constituents under physiologic conditions is more readily apparent between the systemic compartment and the meningeal compartment than between the former and the parenchymal compartment. The meningeal compartment also contains a lymphatic drainage system that allows for the trafficking of immune cells back to the systemic compartment(Da Mesquita, Fu, & Kipnis, 2018). These lymphatic channels can now be identified by magnetic resonance imaging (MRI) in humans(Absinta et al, 2017).Rua et al showed that in animals, recurrent infection in the meninges results in repopulation of this compartment with an expanded repertoire of myeloid cells(Rua et al, 2019).…”
mentioning
confidence: 99%
“…In the glymphatic pathway, CSF flows into the brain along periarterial spaces and subsequently into the brain interstitium, carrying metabolic products from ISF; then, CSF flows toward the perivascular spaces (22,23,46,47,58). In the CSF drainage routes, CSF is transported mainly to meningeal lymphatic vessels or to perineural spaces across the cribriform plate leading to the nasal mucosa (4,13,27,29,39,41) and subsequently into cervical lymph nodes (3,38,42). These findings confirmed the presence of lymphatic vasculature in the brain, which serves as a draining route from brain ISF to peripheral lymph nodes.…”
Section: Introductionmentioning
confidence: 99%